Effects of treatment with haloperidol and clozapine on the plasma concentrations of thyroid hormones in rats - Samadi Afshin (Sciendo, 2020)
Objectives. Psychoactive drugs are group of compounds used to treat severe mental problems, including psychosis, as well as other conditions. This study assessed clinically relevant side effects of haloperidol and clozapine on the thyroid hormones.